2016
DOI: 10.2217/rme-2016-0134
|View full text |Cite
|
Sign up to set email alerts
|

Beneath The Sword Of Damocles: Regenerative Medicine And The Shadow Of Immunogenicity

Abstract: Few topics in regenerative medicine have inspired such impassioned debate as the immunogenicity of cell types and tissues differentiated from pluripotent stem cells. While early predictions suggested that tissues derived from allogeneic sources may evade immune surveillance altogether, the pendulum has since swung to the opposite extreme, with reports that the ectopic expression of a few developmental antigens may prompt rejection, even of tissues differentiated from autologous cell lines. Here we review the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 72 publications
(78 reference statements)
0
13
0
Order By: Relevance
“…A bioengineered construct consists of two components, the cellular compartment and the cell-supporting system, namely the ECM. While a fully developed lab-grown organ consisting in well differentiated cells deriving from a genetically different donor will certainly be subjected to the same well codified immune response as an allograft, it was initially speculated that tissues derived from allogeneic pluripotent stem cells (PSCs)-were not immunogenic and could therefore evade allorecognition [119]. This hypothesis was based on the observation that primordial cells like PSC present low MHC expression and immunogenicity, and that lab-engineered biological constructs lack dendritic cells and a lymphatic system that are primary drivers of alloimmune response.…”
Section: Regenerative Immunologymentioning
confidence: 99%
See 2 more Smart Citations
“…A bioengineered construct consists of two components, the cellular compartment and the cell-supporting system, namely the ECM. While a fully developed lab-grown organ consisting in well differentiated cells deriving from a genetically different donor will certainly be subjected to the same well codified immune response as an allograft, it was initially speculated that tissues derived from allogeneic pluripotent stem cells (PSCs)-were not immunogenic and could therefore evade allorecognition [119]. This hypothesis was based on the observation that primordial cells like PSC present low MHC expression and immunogenicity, and that lab-engineered biological constructs lack dendritic cells and a lymphatic system that are primary drivers of alloimmune response.…”
Section: Regenerative Immunologymentioning
confidence: 99%
“…This hypothesis was based on the observation that primordial cells like PSC present low MHC expression and immunogenicity, and that lab-engineered biological constructs lack dendritic cells and a lymphatic system that are primary drivers of alloimmune response. However, a growing body of literature has clearly shown that PSC are not immune privileged and that even tissues derived from autologous iPS may elicit an inflammatory reaction and succumb to rejection [119]. Therefore, strategies to promote local or systemic tolerance or immunomodulation are currently under investigations.…”
Section: Regenerative Immunologymentioning
confidence: 99%
See 1 more Smart Citation
“…Another important issue when dealing with any allogeneic cell source remains that of immunocompatibility, which is especially critical for PSC-based cell therapies, where the benefits of long-term engraftment would be out-balanced by the risks posed by indefinite immunosuppression in the context of chronic rejection. 67,68 HESC and their progeny are highly immunogenic, and studies in genetically identical mice showed that even a single Mayor Histocompatibility Complex class I gene difference induced some type of rejection. 69 In view of the immunogenicity of hESCs, huge efforts have been placed on the development of banks of HLA-typed hESCs required to achieve partial or full matching between donor and recipient for a large percentage of the population.…”
Section: Stem Cell-derived Rpe Production In Clinical Trialsmentioning
confidence: 99%
“…Notably, albeit still controversial, it has been proposed that reprogramming might lead to re-expression of early developmental antigens for which self-tolerance is not established, posing issues of autoimmune response for autologous hiPSC transplantation. 68 Even more pressing are the concerns around the genetic stability of the cell lines, since the reprogramming itself can pose risks on the genetic and epigenetic integrity of the hiPSCs, which are not all fully understood. 73,74 As a clear example of this concern, a recent clinical trial with hiPS-derived RPE was halted in one patient due to the detection of DNA copy number aberrations in chromosome X of the transplantable cells.…”
Section: Stem Cell-derived Rpe Production In Clinical Trialsmentioning
confidence: 99%